Addictions nursing : scope and standards of practice - American Nurses Association; Fornili, Katherine; Fogger, Susanne; International Nurses Society on Addictions (Silver Spring. MD : American Nurses Association ; Birmingham, Alabama : International Nurses Society on Addictions, 2022)
'Addictions Nursing: Scope and Standards of Practice describes a competent level of nursing care at each level of addictions nursing practice and provides comprehensive overviews of the dynamic and complex practice of the addictions nursing specialty. Jointly published by ANA and the International Nurses Society on Addictions (IntNSA), this book is informed by advances in health care and professional nursing practice. It contains national standards of practice and performance that define the who, what, where, when, why, and how of addictions nursing practice and is a vital reference for: - Quality improvement initiatives - Certification and credentialing - Position descriptions and performance appraisals - Classroom teaching and in-service education programs - Boards of nursing members' orientation programs and regulatory decision-making activities. Addictions Nursing: Scope and Standards of Practice is intended to guide nurses who serve individuals and families affected by substance use and related behaviors, as well as administrators, legislators, regulators, legal counsel, and other interprofessional colleagues. While this document is intended primarily as a reference source for American nurses, it contains valuable information for nurses in other countries'--
Rights Under Laws That Protect Against Discrimination -- Federal Laws That Protect Confidentiality and Privacy -- Code of Ethics and Addictions Nursing -- Provision 1: Compassion and Respect -- Provision 2: Primary Commitment to the Patient -- Provision 3: Advocacy and Protection -- Provision 4: Obligation to Promote Health -- Provision 5: Duties to Self and Others -- Provision 6: Ethical Environment of Work and Engagement -- Provision 7: Advancement of the Profession -- Provision 8: Collaboration With Other Professionals and the Public
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on November 22, 2022).
WorldCat record variable field(s) change: 050
Keywords: Substance abuse -- Nursing -- Standards; Psychiatric nursing -- Standards; Substance-Related Disorders -- nursing; Psychiatric Nursing -- standards; Behavior, Addictive -- nursing; Psychiatric nursing -- Standards; Electronic books; Electronic books